2018
DOI: 10.1159/000490927
|View full text |Cite
|
Sign up to set email alerts
|

Urine Cofilin-1 Detection for Predicting Type 1 Cardiorenal Syndrome in the Coronary Care Unit: A Gold Nanoparticle- and Laser-Based Approach

Abstract: Background: Type 1 cardiorenal syndrome (CRS) is a severe complication for acute decompensated heart failure patients. This study aimed at evaluating the feasibility of using the gold nanoparticle-based localized surface plasmon-coupled fluorescence biosensor (LSPCFB) to detect urine cofilin-1 as a biomarker for predicting CRS among patients in the coronary care unit (CCU). Methods: A total of 44 patients were included with prospectively collected urine and blood samples. Both LSPCFB and conventional enzyme-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Cofilin-1 (CFL1), as actindepolymerizing factors, play an essential role in the dynamics of filaments (34). Other research reported that the gold nanoparticle-based immunoassay localized surface Plasmon-coupled fluorescence biosensor could exploit the potential of urine cofilin-1 as a single biomarker to predict cardiorenal syndrome among coronary care unit patients (35). Dickkopf-related protein 3 (DKK) is a secretory protein involved in vascular smooth muscle cell differentiation and the regulation of myocardial remodeling; however, little is known regarding its role in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cofilin-1 (CFL1), as actindepolymerizing factors, play an essential role in the dynamics of filaments (34). Other research reported that the gold nanoparticle-based immunoassay localized surface Plasmon-coupled fluorescence biosensor could exploit the potential of urine cofilin-1 as a single biomarker to predict cardiorenal syndrome among coronary care unit patients (35). Dickkopf-related protein 3 (DKK) is a secretory protein involved in vascular smooth muscle cell differentiation and the regulation of myocardial remodeling; however, little is known regarding its role in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary cofilin-1 is another intriguing biomarker that acts as a modulator of epithelial-mesenchymal transition or de-differentiated renal tubular cells, which are essential for AKI and renal function recovery [ 71 ], and is related to severity of HF [ 72 ]. The group of Hsing-Yu Chen et al [ 73 ] measured cofilin-1 in 44 patients: 13 patients were diagnosed with CRS, while the other 31 patients were classified into a non-CRS group; they predicted the occurrence of CRS and differentiated CRS patients from non-CRS patients, using the gold nanoparticle-based localized surface plasmon-coupled fluorescence biosensor with a significant accuracy ( p = 0.031; overall accuracy 79.55%).…”
Section: Biomarkers Connecting the Heart And Kidneymentioning
confidence: 99%